Isolation, identification, and enzyme optimization of proteolytic lactic acid bacteria from tuna viscera by-products - YOGA DWI JATMIKO; ARLISA M. R. MUARIF (Society for Indonesian Biodiversity, 2025)
Abstract. Jatmiko YD, Muarif AMR. 2025. Isolation, identification, and enzyme optimization of proteolytic lactic acid bacteria from tuna viscera by-products. Biodiversitas 26: 2762-2772. Fish processing by-products, particularly protein-rich viscera, are underutilized despite their potential to be converted into bioactive peptides using protease enzymes produced by Lactic Acid Bacteria (LAB). This study aimed to isolate proteolytic LAB from tuna viscera, identify the strain with the highest proteolytic activity, and optimize the growth conditions for enhanced protease enzyme production. Proteolytic LAB were isolated from tuna viscera and screened for enzyme activity using skim milk agar and tyrosine-based assays. The isolate with the highest proteolytic activity was identified through 16S rDNA sequencing. Protease production was then optimized using Response Surface Methodology (RSM) based on a Central Composite Design (CCD) with Design-Expert software, evaluating the effects of pH, tuna viscera concentration, and incubation time. The proteolytic potential of 12 LAB isolates from tuna viscera was obtained. The isolate of VT11 showed the highest enzyme activity of 0.55 U mL-1 among the proteolytic LAB strains. After conducting 16S rDNA sequencing, VT11 was identified as Pediococcus pentosaceus, exhibiting 99.72% similarity. Furthermore, RSM analysis identified 24 hours of incubation at pH 5 with 15% tuna viscera as the optimal conditions for protease production by P. pentosaceus VT11.